La Repubblica di Platone nell’esegesi simbolica, e metafisico-teologica di Proclo - Abbate, Michele (ΠΗΓΗ/FONS, 2017)
Among the various themes faced by Proclus in his articulated interpretation of Plato’s Republic, this essay offers an examination of some of those that appear particularly significant in order to understand what direction Proclus’ exegesis of this dialogue takes: the σκοπός (the main argument) and the symbolic system of the Republic (dissertation I); the nature, function and role of justice according to Proclus’ exegesis (dissertations III and VII-VIII); the examination and criticism of the objections raised by Aristotle to Plato’s Republic (dissertation XVII).
Keywords: Proclus; Plato; Aristotle; Republic; skopós; justice